Application of the Basic Principles of Prohibition of Usury and Gharar in Sharia Cooperatives in East Lombok Regency - Cahyadi, Haris; Abdad, M. Zaidi; Bonang, Dahlia (Jurnal Iqtisaduna, 2025)
This study aims to analyze the implementation of the fundamental principles of the prohibition of riba (usury) and gharar (uncertainty) in Islamic cooperatives in East Lombok Regency, as well as the challenges faced during their application. The research employs a descriptive qualitative approach using data collection techniques such as in-depth interviews, observation, and documentation. The findings reveal that Islamic cooperatives in East Lombok have made efforts to implement the prohibition of riba and gharar by Sharia-compliant contracts such as murabahah, mudharabah, and qardhul hasan, supported by supervision from the Sharia Supervisory Board (DPS). However, major challenges remain, including limited understanding among members regarding Sharia contracts, resource constraints in ensuring the presence of transaction objects, and competition with conventional financial institutions offering faster processes. These findings highlight the importance of Sharia financial literacy, continuous education, and strengthening of regulations, as well as the crucial role of the DPS in maintaining consistent adherence to Sharia principles within the cooperatives.